ON THE LIFE-HISTORY AND ECOLOGY OF HORNELLIA MARINA GEN. ET SP. NOV., (CHLOROMONADINEAE), CAUSING GREEN DISCOLORATION OF THE SEA AND MORTALITY AMONG MARINE ORGANISMS OFF THE MALABAR COAST - Subramanian, R (Indian Journal of Fisheries, 2016)
THERE are many published accounts dealing with " red ", " yellow " and" pink " discoloration of the sea water, caused by the occurrence in swarmsof micro-organisms, particularly members of the Dinophyceae (cf. Hayesand Austin, 1951). Some of these organisms are known to affect the fisheryadversely. Green discoloration of the sea, however, has not been recordedfrequently.